ECM Mechanoregulation in Malignant Pleural Mesothelioma - Panzetta, Valeria; Musella, Ida; Fusco, Sabato; Netti, Paolo A. (Frontiers in Bioengineering and Biotechnology, 2022)
Malignant pleural mesothelioma is a relatively rare, but devastating tumor, because of the difficulties in providing early diagnosis and effective treatments with conventional chemo- and radiotherapies. Patients usually present pleural effusions that can be used for diagnostic purposes by cytological analysis. This effusion cytology may take weeks or months to establish and has a limited sensitivity (30%–60%). Then, it is becoming increasingly urgent to develop alternative investigative methods to support the diagnosis of mesothelioma at an early stage when this cancer can be treated successfully. To this purpose, mechanobiology provides novel perspectives into the study of tumor onset and progression and new diagnostic tools for the mechanical characterization of tumor tissues. Here, we report a mechanical and biophysical characterization of malignant pleural mesothelioma cells as additional support to the diagnosis of pleural effusions. In particular, we examined a normal mesothelial cell line (Met5A) and two epithelioid mesothelioma cell lines (REN and MPP89), investigating how malignant transformation can influence cellular function like proliferation, cell migration, and cell spreading area with respect to the normal ones. These alterations also correlated with variations in cytoskeletal mechanical properties that, in turn, were measured on substrates mimicking the stiffness of patho-physiological ECM.